Rotigotine effect in prolonged disturbance of consciousness. Brief report of two cases - Corsi, Fabio Massimo; Gerace, Carmela; Ricci, Monica (Acta Biomedica Atenei Parmensis, 2020)
Two patients with post-coma reactivation deficiency who showed a “dramatic” response to rotigotine therapy are described. They had suffered from prolonged coma due to lesions in the mesencephalic ventral tegmental area. The authors believe that rotigotine effect in these cases could be due to restoration of dopaminergic transmission in medial frontal areas previously “de-afferented” from the lesions. Some comatous patients may experience a prolonged difficulty in recovering a normal state of consciousness. This phenomenon may be due to dysfunction of amynergic activating pathways connecting brainstem to the frontal cerebral cortex. In particular, dysfunction of dopaminergic pathways from the mesencephalon to the frontal cortical areas may be responsible for clinical pictures characterized by preserved alertness and total loss of interactions with the surrounding environment; the so called “waking coma” cases.